Myrmica afghanica (Hymenoptera: Formicidae), a new ant species from Afghanistan - Radchenko, Alexander; Elmes, Graham W. (Zootaxa, 2003)
Myrmica afghanica sp. nov. is described and its taxonomic position is discussed in relation to the unique Myrmica fauna of the Himalayan region. The type specimens were taken in Afghanistan, north of Jäläläbad, in 1948. Based on three workers and a queen, it is most similar to the species of the rubra-group.